Polymorphisms of the Tissue Factor Pathway Inhibitor (TFPI) Gene in Patients With Acute Coronary Syndromes and in Healthy Subjects: Impact of the V264M Substitution on Plasma Levels of TFPI - Moatti, Didier; Seknadji, Patrick; Galand, Colette; Poirier, Odette; Fumeron, Frederic; Desprez, Sophie; Garbarz, Michel; Dhermy, Didier; Arveiler, Dominique; Evans, Alun; Luc, Gerald; Ruidavets, Jean-Bernard; et al. (Arteriosclerosis, thrombosis, and vascular biology, 1999)
Mutations of the gene encoding tissue factor pathway inhibitor (TFPI), an inhibitor of TF-induced activation of the coagulation cascade, were screened for in 130 patients and 142 healthy controls to determine whether these variants contribute to acute coronary syndromes or modify plasma TFPI levels. The following 3 new polymorphisms were identified384T[right arrow]C in exon IV, which does not change the corresponding amino acid (tyrosine 57); -33C[right arrow]T in intron 7 (the T/T, C/T, and C/C genotypes were found in [approximate]50%, 40%, and 10% of subjects in both groups); and 874G[right arrow]A in exon IX (GTG[right arrow]ATG), which predicts a valine to methionine change (V264M) in the carboxy-terminus tail of TFPI. The V264M polymorphism was found in 9.2% of the cases and 4.9% of the controls; the associated odds ratio (OR) for acute coronary syndromes was 2.0 (95% confidence interval [CI], 0.7 to 5.1). The OR increased to 3.6 (95% CI, 0.8 to 15.7) and 3.2 (95% CI, 0.9 to 11.8) in nonsmokers and patients without other risk factors, respectively. The possible link between the V264M polymorphism and coronary heart disease was checked in a large case-control study of myocardial infarction (Etude Cas-Temoins de l'Infarctus du Myocarde [the ECTIM Study]). The results showed no link between the V264M polymorphism and coronary syndromes. Interestingly, however, 5 patients heterozygous for the V264M polymorphism had significantly lower plasma TFPI levels than did 13 patients with the most common genotype. Although our present results do not support an association between TFPI polymorphisms and acute coronary syndromes, the possibility that 1 of them, especially the exon IX polymorphism, is associated with subtypes of myocardial infarction or to evolutive particularities that were not assessed in this study, cannot be excluded and is currently being evaluated. (Arterioscler Thromb Vasc Biol. 1999;19:862-869.)